Transmissão vertical do HIV em população atendida no serviço de referência em Maceió - Alagoas - Rodrigues, Sueli Teresinha Cruz [UNIFESP] (2010)
Introduction: the evolution of the Acquired Immunodeficiency Syndrome epidemic in Brazil brought a challenge to control the Human Immunodeficiency Virus (HIV) vertical transmission. The vertical or mother-child transmission of HIV is a route exposure which has multiple causes and the influence of factors associated with transmission of the virus varies according to the studied populations. Objectives: to identify the HIV vertical transmission rate in a reference service unit in the municipality of Maceió - Alagoas in a four-year period, to evaluate the maternal and fetal factors involved in the HIV vertical transmission and to identify pre-natal care, at delivery and birth follow-up actions related to the reduction of vertical transmission. Method: observational descriptive transversal retrospective study, evaluating 102 medical records of HIV positive women and their exposed children assisted by a specialized service unit in a four-year-time period. Results: Approximately 6.6% of children were infected, their mothers were aged 20 to 39 years and 66.6% had low formal education level, 40% did not attend any kind of pre-natal care service, 16.7% of their partners were unaware of their serologic condition; 5.9% of these women had sexual intercourse with multiple partners. Mothers of 75% of the infected children did not undergo prophylaxis with antiretroviral (ARV) and viral load test during pre-natal care. There was a higher percentage of children who did not initiate the prophylaxis with antiretroviral in the infected groups and a tendency for a higher percentage (50.0%) that was breastfed in the same group (p- 0.058). There was a higher percentage of women (84.10%) who used ARV during childbirth and children (91.5%) who started prophylaxis with ARV within the first 24 hours in the non-infected group. Conlusion: it was observed that the incidence of HIV vertical transmission in the reference service unit in the municipality of Maceió - Alagoas in a four-year-time period selected for the study (January 2002 to December 2006) was 6.6%. Those infected children did not have the opportunity for prophylaxis of HIV vertical transmission, which ratifies the urgency of an increase in the anti-HIV tests availability for pregnant women and supervision of the actions. Concerning the vertical HIV transmission, actions that address education, mainly of the young people and the use of condom during sexual intercourse are still fundamental. By means of such actions as well as prophylaxis of the vertical transmission, even if it is not possible to eliminate HIV infection in the pediatric population, we will, at least, transform such conditions in a matter of lesser extent, potentially controlled by the Public Health Department.